2016
DOI: 10.4238/gmr.15027994
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD36 expression and polymorphism with serum biochemical indices in Cherry Valley duck

Abstract: ABSTRACT. Cluster of differentiation 36 (CD36) plays a crucial role in lipid sensing, innate immunity, atherogenesis, and glycolipid metabolism. This aims of this study were to delineate the CD36 mRNA expression profile in 16 duck tissues using relative quantitative realtime PCR and to screen single nucleotide polymorphisms (SNPs) in the duck CD36 gene by PCR-single strand conformation polymorphism and DNA direct sequencing. In addition, this study investigated CD36 gene expression, genetic variation, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recent research has shown that CD36 is involved in the regulation of calcium levels, phospholipase activation, and eicosanoid generation 8 - 11 . CD36 variants had been associated to blood lipid levels alterations as well to susceptibility to the metabolic modi cations 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that CD36 is involved in the regulation of calcium levels, phospholipase activation, and eicosanoid generation 8 - 11 . CD36 variants had been associated to blood lipid levels alterations as well to susceptibility to the metabolic modi cations 12,13 .…”
Section: Introductionmentioning
confidence: 99%